Fighting Islamic Radicalism Through Religious Moderatism in Indonesia: An Analysis of Religious Movement - Kunawi Basyir (UIN Sunan Kalijaga Yogyakarta, 2020)
The Indonesian socio-religious circumstances have been complicated lately, especially since the reformation era. This situation is marked by turmoils, horizontal conflicts, and unfriendly political dynamics involving radical religious and political ideology (henceforth: radical Islamic groups). Against this backdrop, this research is an attempt at getting a comprehensive understanding of radical islamic movements as well as the strategy of coping with them. The method employed is participatory action research, with Surabaya is selected as its setting. This study finds that re-upholding local tradition framed with religious moderation concept that have for years been the trademark of Indonesian Islam, which is manifested through distinctive local practices labelled as Islam Nusantara (henceforth: Islam wasatiyya), is capable of minimises the radical Islamic movements that has growth as a threat for the nation.